2001
DOI: 10.1001/archpsyc.58.4.353
|View full text |Cite
|
Sign up to set email alerts
|

Differential Circadian Rhythm Disturbances in Men with Alzheimer Disease and Frontotemporal Degeneration

Abstract: Background: Caregiver exhaustion is a frequent consequence of sleep disturbance and rest-activity rhythm disruption that occurs in dementia. This exhaustion is the causal factor most frequently cited by caregivers in making the decision to institutionalize patients with dementia. Recent studies have implicated dysfunction of the circadian pacemaker in the etiology of these disturbances in dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
111
0
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(118 citation statements)
references
References 54 publications
4
111
0
3
Order By: Relevance
“…The few studies which investigated the emotional phenotypes of FTD tau models describe decreased reward-seeking behaviour and increased forced swim test immobility, which Potentially as a result of altered emotionality, PLB2 Tau mice demonstrated a robust hypoactive trait in many experimental parameters, most evident when monitoring circadian and ambient activity within the PhenoTyper. In this respect PLB2 Tau mice present a similar global reduction in activity as observed in human FTD (Harper et al, 2001;Anderson et al, 2009). Hypoactivity and inertia being most pronounced during the initial waking hours, which was also observed here in PLB2 Tau mice.…”
Section: Emotional Phenotypes Of Plb2 Tau Micementioning
confidence: 69%
“…The few studies which investigated the emotional phenotypes of FTD tau models describe decreased reward-seeking behaviour and increased forced swim test immobility, which Potentially as a result of altered emotionality, PLB2 Tau mice demonstrated a robust hypoactive trait in many experimental parameters, most evident when monitoring circadian and ambient activity within the PhenoTyper. In this respect PLB2 Tau mice present a similar global reduction in activity as observed in human FTD (Harper et al, 2001;Anderson et al, 2009). Hypoactivity and inertia being most pronounced during the initial waking hours, which was also observed here in PLB2 Tau mice.…”
Section: Emotional Phenotypes Of Plb2 Tau Micementioning
confidence: 69%
“…Of note, the delayed body temperature minimum in old mouse lemurs contrasts with the phase advance typical of old humans (Monk et al, 1995;Duffy et al, 1998). On the other hand, a delay in body temperature has been observed in demented elderly subjects (Harper et al, 2001), and Duffy et al (Duffy et al, 1998) demonstrated that the body temperature nadir was actually delayed when expressed relative to the waking onset in the elderly. In mouse lemurs, the body temperature minimum was affected by photoperiod but not by age, while the timing of minimal body temperature changed according to age but not photoperiod.…”
Section: ()mentioning
confidence: 98%
“…Van Someren et al (17) reported that rhythms were most fragmented in institutionalized AD patients and that higher levels of daytime activity predicted more coherent rhythms, whereas lower levels of daytime activity predicted rhythm fragmentation. Changes in circadian parameters are not equivalent across different types of dementias; there are differences in the nature and magnitude of rhythm disturbance in AD, frontotemporal dementia, and diffuse Lewy body disease (18). The overall locomotor changes that occur in AD seem to be related to more specific behavioral changes, for example in meal time, which in turn might be linked to poorer nutritional outcomes (19).…”
Section: Functional Studies Of Circadian Disruption In Admentioning
confidence: 99%